ISSUES OF APPLICATION OF ARTIFICIAL INTELLIGENCE IN CLASSIFICATION OF ELECTRIC CARS ACCORDING TO COMMODITY NOMENCLATURE OF FOREIGN ECONOMIC ACTIVITY BASED ON COMPLEX INSPECTION SYSTEM (Modern education and development, 2025)
In the article, the methods of automatic analysis and classification of goods and vehicles by means of Complex Inspection System (CIS) images are currently implemented on the basis of artificial intelligence (AI) systems, using the experience of Russia, China, Australia, the USA, Finland, Estonia, Turkey and Japan. Based on this, the issue of systematic classification according to the Commodity Nomenclature of Foreign Economic Activity (CN FEA) by means of intelligent recognition based on physical, external, electronic data, in the automatic analysis of its image data, in the identification of CIS electric vehicles (EV) for customs purposes, is highlighted.